Kindness Character Profile of Students at SMP-IT Daarul Amiin - Silmi Nauriatul Hasanah; Aam Imaddudin; Feida Noorlaila Isti’adah (Mauve Journal De Leardu, 2025)
This study aims to describe the kindness character profile of students at SMP-IT Daarul Amiin. Kindness is one of the character strengths that supports students' emotional well-being, positive peer interactions, and healthy behavior in the school environment. This study used a descriptive quantitative method with a saturated sampling technique involving 154 students (87 males and 67 females). The data were collected using a kindness scale consisting of six dimensions: generosity, nurturance, care, compassion, altruistic love, and niceness. The results showed that the overall level of kindness character among students was in the moderate category. The care dimension scored the highest, while the nurturance dimension scored the lowest. Based on statistical analysis, there was no significant difference in kindness character based on gender. These findings indicate that kindness character development needs to be strengthened through psychoeducational strategies in guidance and counseling services to support students' holistic personal and social growthThis study aims to describe the kindness character profile of students at SMP-IT Daarul Amiin. Kindness is one of the character strengths that supports students' emotional well-being, positive peer interactions, and healthy behavior in the school environment. This study used a descriptive quantitative method with a saturated sampling technique involving 154 students (87 males and 67 females). The data were collected using a kindness scale consisting of six dimensions: generosity, nurturance, care, compassion, altruistic love, and niceness. The results showed that the overall level of kindness character among students was in the moderate category. The care dimension scored the highest, while the nurturance dimension scored the lowest. Based on statistical analysis, there was no significant difference in kindness character based on gender. These findings indicate that kindness character development needs to be strengthened through psychoeducational strategies in guidance and counseling services to support students' holistic personal and social growth.